Effect of Simvastatin Alone and in Combination With Cytosine Arabinoside on the Proliferation of Myeloid Leukemia Cell Lines. (1st July 2001) - Lishner, Michael; Bar-Sef, Avigdor; Elis, Avishay; Fabian, Ina
Abstract : Background: Cholesterol biosynthesis is regulated by the activity of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. Cholesterol and its derivatives are required in high concentrations by neoplastic proliferating cells for both DNA synthesis and cell growth. Thus, inhibition of HMG-CoA reductase could effect cell cycle progression and proliferation. Therefore, we examined the effect of an HMG-CoA reductase inhibitor (simvastatin) alone and in combination with cytosine arabinoside (ARA-C) on the proliferation of two AML cell lines. Methods: AML blasts derived from two cell lines (HL-60 and AML-2) were incubated with increasing concentrations of either simvastatin alone or simvastatin alone for 24 hours with ARA-C added thereafter. The effect of the drugs on cell proliferation in liquid culture ( 3 H thymidine uptake) and on clonogenic assay was analyzed. Results: We found that the number of proliferating AML blasts (suspension cultures) and colony formations (agar cultures) of both cell lines declined significantly after incubation with simvastatin. Preincubation of both cell lines with simvastatin by the addition of increasing concentrations of ARA-C produced a degree of growth inhibition that was significantly greater than that of the individual compounds. This antigrowth interaction was additive rather than synergistic. Conclusions: We conclude that simvastatin has a major antiproliferative effect on AML blasts in vitro. Also, the combination of simvastatin and ARA-C significantly enhanced the antiproliferative effect of each drug. These findings may open new avenues in both the laboratory and clinical research of the treatment of leukemia.